FlumeRide: Interactive Space Where Artists and Fans Meet-and-Greet Using Video Calls - Minju Kim; Heejeong Ko; Jonghun Choi; Jungjin Lee (IEEE Access, 2023)
Recently, artists and fans meet more often online owing to the COVID-19 pandemic. Therefore, fans need to engage closely with artists and enjoy rich content. FlumeRide is a mobile application that helps artists and fans meet and greet through video calls. Beyond simply connecting the two, it provides detailed features similar to that fans experience in face-to-face meetings. We first investigated the overall contexts and challenges faced by fans during online meet-and-greets and derived the design elements. Then, we designed and implemented a system that supports various communications and contents in situations before, during, and after the conversation between fans and artists. FlumeRide incorporates various features to support communications in highly immersive and efficient ways, such as chat, video calls, streaming, and recordings. Our user study results demonstrate that FlumeRide enables fans to have private video calls with artists and experience rich interactions.